Advances in Surface Plasmon Resonance-Based Biosensor Technologies for Cancer Cell Detection. (9th September 2022) - Karki, Bhishma; Uniyal, Arun; Pal, Amrindra; Srivastava, Vivek
Abstract : Efforts have been made to enhance the surface sensitivity of the conventional surface plasmon resonance biosensor. To improve the sensitivity, a unique two-dimensional heterostructure layer of titanium disilicide and black phosphorus layer has been deposited over the metal surface. The titanium disilicide (TiSi2 ) nanosheet is placed in between silver (Ag) and black phosphorus (BP) films in the Kretschmann arrangement. This biosensor executes better over a wide range of refractive index variations, including biological cell distribution in individual blood. It may become a fast method of detecting cancerous cells and the several variants of corona and other viruses that become pandemic. Using the finite element method-based simulation technique, the sensitivity obtained as 195.4 degree/RIU, 167.6 degree/RIU, 212.4 degree/RIU, 168.4 degree/RIU, 212.4 degree/RIU, 186.6 degree/RIU, 218.6 degree/RIU, 195.4 degree/RIU, 203.6 degree/RIU, 202.6 degree/RIU 203.6 degree/RIU, and 202.6 for basal (skin cancer), basal (normal cell), HeLa (cervical cancer), MCF-7 (breast cancer), HeLa (normal cell), Jurkat (blood cancer), Jurkat (normal cell), PCI-2 (adrenal gland cancer), PCI-2 (normal cell), MDA-MB-231 (breast cancer), MDA-MB-231 (normal cell), MCF-7 (breast cancer), and MCF-7 (normal cell), respectively, and other performance parameters such as detection accuracy, figure of merit, and full width and half maximum (FWHM) are also evaluated.